PENERAPAN FISIOTERAPI DADA PADA ANAK PRA SEKOLAH (3-6 TAHUN) DENGAN MASALAH KETIDAKEFEKTIFAN BERSIHAN JALAN NAFAS AKIBAT ISPA DI RSUD BAYU ASIH PURWAKARTA - Rina Fera,; Sherly, Sherly; Syifa Nurlatifah, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
Respiratory tract diseases are one of the main causes of death in children, one of which is ARI. ARI is an acute infectious disease that attacks one or more parts of the respiratory tract from the nose to the alveoli. Based on the prevalence of ISPA in 2016 in Indonesia, it has reached 25% with an incidence range of around 17.5% - 41.4% with 16 provinces having a prevalence above the national figure. Apart from that, ISPA is also often on the list of the 10 most common diseases in hospitals and places ISPA as the biggest cause of infant death in Indonesia. Patients with ISPA need to be given chest physiotherapy therapy. Chest physiotherapy is to prevent buildup in the lungs and can clear the airways. Chest physiotherapy is very effective in removing secretions from the lungs and increasing ventilation in patients with impaired lung function. The aim of this research is to help overcome the problem of ineffective airway clearance in An.C who experience ARI. This type of research is descriptive with a case study approach method. The subject in this study was a preschool child patient (3-6) years old who experienced acute respiratory infections in the Kemuning ward of Bayu Asih Regional Hospital, Purwakarta. The results of this study showed that the child's breathing before chest physiotherapy was 34 and after chest physiotherapy for 3 days was 22. The chest physiotherapy nursing intervention was carried out in the morning for 20 minutes. The conclusion from this study was that there was a significant difference in the average respiratory frequency before and after chest physiotherapy procedures were carried out in children